REVIEW OF BIOPHILIC DESIGN RESEARCH DEVELOPMENTS ON TRENDS, GAPS, AND FUTURE OPPORTUNITIES - Pande, Artha; Dewi Larasati (International Journal on Livable Space, 2026)
Biophilic design has become a prominent approach in contemporary architecture. It aims to enhance human health, well-being, and productivity by integrating natural elements into the built environment. However, despite its growing popularity, current biophilic design research and applications largely rely on universal principles and often overlook ecological and cultural contexts, particularly in non-Western, tropical, and urban regions such as Southeast Asia. Aims: This study aims to examine the global development of biophilic design research by identifying major trends, research gaps, and future research opportunities. Methodology and results: A summative content analysis was conducted on 90 highly cited articles published in indexed national and international journals between 2014 and 2024. The findings indicate that existing studies predominantly focus on direct and indirect experience of nature, while the experience of space and place, especially aspects related to cultural and ecological attachment to place, remains underexplored. Conclusion, significance, and impact of the study: The findings highlight a critical research gap in context-sensitive biophilic design approaches. This study underscores the importance of developing regenerative biophilic design models that incorporate local wisdom, cultural identity, and ecological specificity. These models provide a foundation for future research and design practices that are both globally informed and locally responsive.